Enhancement of Knowledge and Internalization of Culture Through Employee Training at RS Islam Surabaya - Budhi Setianto; Agus Aan Adriansyah; Yauwan Tobing Lukiyono; Hartatik Nila Karmila; Effendi Effendi; Nikmatus Sa’adah (UNUSA Press, 2025)
The addition of employees at the Surabaya Islamic Hospital means that they don't know each other, the difference in generations is one of the clashing problems related to communication. If this problem is left unchecked, it is possible that conflicts will often occur, and teamwork will not be formed in accordance with the organization's expectations. Objectives: community service is to organize cultural internalization workshops and routine exercise programs aimed at creating a pleasant work atmosphere. The informal happy atmosphere aims to foster good teamwork between employees. The implementation method is to provide workshops to increase employee culture internalization and exercise. Based on the results of this workshop, there was an increase in knowledge of 14.2%. There is a significant difference between the Pre Test and Post Test based on the results of the Paired Sample T-Test with an Apha of 5%.